ESP (ENGLISH FOR SPECIFIC PURPOSE): TEACHING LEGAL ENGLISH USING LEXICAL APPROACH - Supardi Supardi (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Legal English (LE), like such other ESPs as Business English, Medical English, Nursing English, English for Accounting, English for Aviation, English for Banking, and many others, has a large number of specific words that the learners of English as a Foreign Language (EFL) need to acquire. In term of LE, it is necessary for the EFL learners, especially those of law students, to master the specific vocabularies frequently used in legal settings. Without having enough mastery of LE vocabularies, it is certainly difficult for them to use their English skills in legal context such as reading or writing legal documents, listening to the legal reports or news from radio or from television, and presenting the case in the courtroom. To meet their need for the acquisition of LE vocabularies, it is therefore important for the EFL teachers (especially those teaching English to law students) to use a certain approach called lexical approach for his or her teaching in the classrooms. With this approach, they are hopefully able to develop the EFL leaners’ acquisition of LE vocabularies. In the framework of this development, this paper will then focus its discussion on understanding of LE, overview of lexical approach, importance of lexical approach to teaching LE, exploration of LE vocabularies for teaching materials, and samples of teaching materials design of LE vocabularies.